Probiotics study with Streptococcus salivarius and its ability to produce bacteriocins and adherence to KB cells - Vera FANTINATO; Heloísa Ramalho CAMARGO; Ana Lúcia Orlandinni Pilleggi de SOUSA (Universidade Estadual Paulista, 2019)
Abstract Introduction Streptococcus salivarius is a dominant oral species and the best suitable candidate for probiotic of the oral cavity. Since Streptococcus salivarius is able to produce bacteriocins against Streptococcus pyogenes interest has been focused on the use of it as a probiotic to avoid sore throats by Streptococcus pyogenes. Objective This study is for selecting Streptococcus salivarius strains for potential use as probiotics for the oral mucosa, that is, production of bacteriocin against Streptococcus pyogenes and the ability to bind to KB cells. Material and method Tongue material from 45 students was collected and seeded on Mitis Salivarius Agar plaques. The strains were tested by the production of bacteriocin-like substances (BLIS) against S. pyogenes, biochemically and PCR for identification of S. salivarius. The best strains were tested for adherence to KB cells. Briefly, S. salivarius strains were cultured in broth, washed and suspended at 108cells/ml. KB cells were inoculated into plaques, washed and incubated with the bacteria, for adhesion. These were washed for lysis of the KB cells and release bacteria for determination of CFU. Result The bacteriocin test showed that 133 strains presented inhibition of S. pyogenes. The samples tested for adhesion to KB cells, presented different profiles and only three strains presenting high adhesion capacity. Conclusion The selection of strains of Streptococcus salivarius with high inhibitory activity against Streptococcus pyogenes, as well as adherence to KB cells leads us to the next future step, that is, to use the best strains for in vivo colonization tests